The Impact of Digital Content Quality and Short-Video Marketing on Brand Awareness and Engagement Rate among Fashion MSMEs in West Java - Sulistyo Budi Utomo; Paramita Andiani; Dila Padila Nurhasanah (West Science Social and Humanities Studies, 2026)
The rapid growth of social media platforms has transformed marketing strategies among fashion Micro, Small, and Medium Enterprises (MSMEs), particularly through the use of digital content and short-form video promotion. This study aims to examine the impact of digital content quality and short video marketing on brand awareness and engagement levels among fashion MSMEs in West Java. A quantitative research design was employed using survey data collected from 155 MSME owners and managers through a structured questionnaire measured on a Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that digital content quality has a positive and significant effect on brand awareness and engagement levels, while short video marketing significantly enhances both brand visibility and audience interaction. Brand awareness also demonstrates a significant positive influence on engagement and acts as a partial mediating variable between digital marketing strategies and engagement outcomes. These findings suggest that visually appealing and informative content combined with short video formats can strengthen brand positioning and improve customer interaction in digital environments. This study contributes to digital marketing literature by providing empirical evidence from the fashion MSME sector in West Java and offers practical insights for businesses seeking to optimize their social media strategies in competitive markets.